1979
DOI: 10.1073/pnas.76.6.3006
|View full text |Cite
|
Sign up to set email alerts
|

Morphine and endorphins modulate dopamine turnover in rat median eminence.

Abstract: There is evidence that some of the actions of both endogenous and exogenous opioids (e.g., stimulation of prolactin release) are mediated by interaction with catecholaminergic systems. Morphine (1.67, 5, and 15 mg/kg of body weight, intraperitoneally) altered dopamine turnover as measured by the a-methyl-p-tyrosine method in the median eminence, neostriatum, and frontal cortex of male Sprague-Dawley rats. The turnover rate of dopamine was reduced in the median eminence and frontal cortexbut accelerated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(52 citation statements)
references
References 31 publications
4
47
1
Order By: Relevance
“…were needed in order to obtain a significant effect on this parameter (Garcia-Sevilla et al, 1980). The ~-MPT-induced disappearance of dopamine from the cortex and from the median eminence was found to be decreased by D-Ala2-D-LeuS-enkephalin by Deyo et al (1979). This latter obserw~tion is in accordance with results of a microfluorometric study of the ct-MPT-induced disappearance of formaldehyde-induced catecholamine fluorescence from substructures of the median eminence.…”
Section: Interaction With Brain Catecholam1nessupporting
confidence: 79%
See 1 more Smart Citation
“…were needed in order to obtain a significant effect on this parameter (Garcia-Sevilla et al, 1980). The ~-MPT-induced disappearance of dopamine from the cortex and from the median eminence was found to be decreased by D-Ala2-D-LeuS-enkephalin by Deyo et al (1979). This latter obserw~tion is in accordance with results of a microfluorometric study of the ct-MPT-induced disappearance of formaldehyde-induced catecholamine fluorescence from substructures of the median eminence.…”
Section: Interaction With Brain Catecholam1nessupporting
confidence: 79%
“…Striatal dopamine turnover, as measured from the rate of dopamine disappearance following inhibition of tyrosine hydroxylase with ~-MPT, was found to be increased after the i.c.v, administration of 25 pg D-AlaZ-Met-enkephalinamide (Calderini et al, 1978) and D-Ala2-D-LeuS-enkephalin (Deyo et al, 1979). Schwarcz et al (1979), on the other hand, reported that Met-enkephalin, given as an i.c.v, infusion of approximately 50 pg over a period of one hr in a total volume of 60/21, did not affect the ~-MPT-induced disappearance of dopamine fluorescence from dopamine terminals in the caudate nucleus.…”
Section: Interaction With Brain Catecholam1nesmentioning
confidence: 99%
“…Systemically or locally administered synthetic and locally administered natural peptidic kappa-opioid receptor agonists (ie dynorphin) inhibit dopamine release in the mesolimbicmesocortical dopaminergic systems (Di Chiara and Imperato, 1988;Spanagel et al, 1990;Claye et al, 1997;Zhang et al, 2004a, b). While mu-and kappa-opioid receptor antagonists can each reverse these effects, neither administered alone have been shown to alter dopamine release in either rodent or non-human primate models (Deyo et al, 1979;Durham et al, 1996;Butelman et al, 2002). One possible exception is a positron emission tomography (PET) study in rats, which found increased binding potential in the striatum of the displaceable dopamine D1 ligand [ 11 C]SCH23,390 following acute but not chronic nalmefene administration (Unterwald et al, 1997).…”
Section: Dopamine and The Mu-and Kappa-opioid Systemsmentioning
confidence: 99%
“…Opioids act on a hypothalamic level, although a direct effect on the pituitary has not been completely excluded (Enjalbert et al, 1979). Endogenous opioid peptides and synthetic opiates suppress TH activity and m-RNA levels in the TIDA neurons (Arbogast and Voogt, 1998;Deyo et al, 1979;Reymond et al, 1983;Andrews and Grattan, 2003). Therefore, one established mechanism of opioid-induced PRL secretion is through inhibition of TIDA neuronal activity, probably modulated by the opioid receptor subtypes m and k (see review, Ben-Jonathan, 1994;Soaje and Deis, 1994).…”
Section: Modulatorsmentioning
confidence: 99%